Insulin receptor is phosphorylated in response to treatment of HepG2 cells with insulin-like growth factor I. - Duronio, V (1990)
1. Binding of insulin and insulin-like growth factor I (IGF-I) to HepG2 cells was analysed with regard to competition by both insulin and IGF-I. At concentrations of insulin that caused maximal phosphorylation of the insulin receptor, virtually no displacement of IGF-I binding was observed. Similarly, at concentrations of IGF-I that caused maximal phosphorylation of the IGF-I receptor, no displacement of insulin binding was observed. 2. When the phosphorylation of both receptors was examined individually by using specific monoclonal antibodies to immunoprecipitate the receptors, phosphorylation of the insulin receptor was found to increase on both serine and tyrosine residues in cells treated with 100 ng of IGF-I/ml. In contrast, no increased phosphorylation of IGF-I receptor was observed in cells treated with 100 ng of insulin/ml. 3. The increase in phosphorylation of insulin receptor in response to IGF-I correlated with the dose-response of IGF-I-stimulated phosphorylation of the IGF-I receptor. 4. The IGF-I-stimulated phosphorylation of the insulin receptor could be blocked by preincubation with a monoclonal antibody that blocks IGF-I binding to the IGF-I receptor.